Phylogeography of Labyrinthula species and strains shows high connectivity and low genetic variation across seagrass hosts and geographic locations in North America - Pagenkopp Lohan, Katrina M.; DiMaria, Ruth; Martin, Daniel L.; Hughes, A. Randall; Peterson, Bradley J.; Boyer, Katharyn E.; Stachowicz, John J.; Jorgensen, Pablo; Ruiz, Gregory M.; Ross, Cliff (Frontiers in Marine Science, 2025)
Seagrass wasting disease, caused by parasitic slime nets in the genus Labyrinthula, affects seagrasses globally with outbreaks occurring at local to regional scales. Though prior research showed variation in pathogenicity across strains, little is known about the broad-scale diversity and biogeography of Labyrinthula species. We used targeted amplicon-based high throughput sequencing (HTS) to examine the phylogeography of Labyrinthula species associated with two seagrass hosts (Zostera marina, Thalassia testudinum) collected from across North America, including locations in the USA and Mexico. After testing 189 seagrass blades from 16 locations across North America, Labyrinthula spp. were detected at 14 sites with PCR prevalence ranging from 20 - 100%. We generated 10,936,628 sequences for analyses, which yielded 25 unique Labyrinthula amplicon sequence variants (ASVs), which were phylogenetically grouped into three species of Labyrinthula. All three species detected were previously identified as pathogenic, indicating that Labyrinthula species capable of causing wasting disease are present across these regions, including in locations where disease outbreaks have not been reported. The highest strain level variation was detected in Florida, which is likely due to larger sample sizes from Florida compared to other sampling locations. Assessing the phylogeography of strains was limited by sample size in each location, but indicates that the genetic connectivity of strains appears high, with location and seagrass host being the most important factors explaining the variation in Labyrinthula strains detected. The high connectivity, but low overall species diversity of Labyrinthula, is consistent with a parasite that is a host generalist. Given the high connectivity of strains and broad geographic range of pathogenic Labyrinthula reported here, this study provides valuable insight regarding how parasite diversity impacts seagrass disease.